Primary mucosal malignant melanoma of the nasal cavity - Mukhopadhyay, Subrata; Haque, Misbahul (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2020)
Primary mucosal melanoma of the nasal cavity and paranasal sinuses is a very aggressive and rare disease with only about 0.5 % of malignant melanoma arising from the nasal cavity. There are only few reports from India. We report a rare case of sino-nasal mucosal malignant melanoma in a 58 years old female who presented with blackish coloured sino-nasal mass involving right nasal cavity, spontaneous and recurrent epistaxis and obliteration of the right naso-labial fold with occasional pain in the past 10 months. Contrast enhanced computed tomography scan showed a heterogenous mass involving right nasal cavity, right maxillary antrum and right ethmoidal area. A positron emission tomography computed tomography was also done which showed increased uptake in the region mentioned above. Initial biopsy, the mass was diagnosed as malignant melanoma. Total maxillectomy was performed with plan of post-operative radiotherapy.